The emotional voter: the impact of electoral campaigns and emotions on electoral behaviour in Britain - Kiss, C (2013)
This thesis examines the role of emotions in mediating the effects electoral campaigns have on political behavior in Britain. I contend that electoral campaigns, aside from direct effects, can also have indirect effects, manifested through the impact of the emotions they induce. I theorize that, through manipulating the tone, framing and targeting of their messages, electoral campaigns induce specific emotions. Emotions are argued to have a direct effect on turnout (intentions) and a moderating effect on the impact partisanship, policy preference and leader evaluations have on vote choice. Extending the Theory of Affective Intelligence, I hypothesize that individuals who are enthusiastic about their preferred party, or experience anxiety or anger in relation to an out-party, are more likely to turn out, and to cast their vote based on their partisanship. Contrarily, anxiety and anger experienced towards the preferred party are expected to decrease the importance of partisanship and increase the relevance of policy preferences and leader evaluations when voting. While anger experienced towards this party is also hypothesized to also decrease turnout, anxiety is not thought to affect it. To test these propositions, I rely on a multi-methodological approach that uses both panel and experimental data. The panel data was collected in two waves prior to the 2010 British General Election. The laboratory experiment, designed to specifically test the emotion-induction capacity of campaigns, was conducted on British participants in the aftermath of the same elections. The results corroborate the theory. First, the analyses confirm that campaigns, not only can, but actually do induce emotions. Second, it is shown that emotions do influence political behavior as expected. Third, it is established that the effect of the campaign on turnout intentions is partly channeled through emotions. Finally, it is shown that campaign exposure indirectly affects vote choice by increasing the magnitude of the impact emotions have on the effect of partisanship on vote choice. Aside from the literature on campaign effects in Britain, the thesis also contributes to the emerging literature pertaining to the role of emotions in politics. Moreover, it contributes to the field of voting behaviour by extending our understanding of the psychological underpinnings of vote choice.